Sisters - Telgemeier, Raina; Lamb, Braden (New York Graphix, 2014)
Three weeks. Two sisters. One car. A true story
Comic strips
2 13 23
Keywords: Telgemeier, Raina; Brothers and sisters -- Comic books, strips, etc